Analysis of the Effect of Company Size, Liquidity, and Capital Structure on Company Value with Profitability as a Mediating Variable in Banks Listed on the Indonesia Stock Exchange in 2021-2023 - Maria Melania Manafe; Stanis Man; Yolinda Yanti Sonbay; Henny A. Manafe; Paskalis Seran (International Journal of Economics Development Research (IJEDR), 2026)
Company value in the banking context plays a crucial role because it reflects the success and financial health of the company. This indicates the level of trust of shareholders, clients, and financial services authorities in the bank's performance and integrity. With high corporate value, banks can attract investors, maintain liquidity, and better face market challenges. This study aims to analyze the description of company size, liquidity, capital structure, profitability, and corporate value in banks listed on the Indonesia Stock Exchange. In addition, this study examines the effect of company size, liquidity, and capital structure on corporate value and profitability. This study also analyzes the effect of profitability as a mediating variable in the relationship between company size, liquidity, and capital structure on company value in banks listed on the Indonesia Stock Exchange. This study is an explanatory quantitative study. The results show that, descriptively, banks listed on the Indonesia Stock Exchange generally have large company size, relatively safe liquidity levels, varied capital structures, fairly good profitability, and varying company values according to investor perceptions. Empirically, firm size and liquidity have a positive and significant effect on firm value, while capital structure has a negative and significant effect on firm value. Profitability has been shown to have a positive and significant effect on firm value. Furthermore, firm size has a positive and significant effect on profitability, while liquidity has a negative and significant effect on profitability, and capital structure has a negative and significant effect on profitability. The mediation test results show that profitability partially mediates the relationship between company size and company value, but does not mediate the relationship between liquidity and capital structure on company value. The R-square value shows that the independent variables are able to explain 22.8% of profitability and 16.9% of company value, indicating that the explanatory power of the model is in the moderate category.